All God's People Facing the Same Way: A Theology of Discipleship Shaped by Disciples—an Anglican Perspective. Issue 2 (November 2015) - Jordan, Elizabeth
Abstract : This article is one contribution to the discussion of discipleship encouraged by the Archbishop's Council in the Church of England. It contains the substance of a talk given on 'the theology of discipleship' to a day conference on 29 April 2015 organized by the Ministry Division and the Anglican Adult Education Network. The article also contains an examination of the sources of that theology and shows how sharing in worship and study of the Bible with Christian disciples have shaped the ideas which were presented. It is thus an example of 'relational epistemology', the knowledge gained through participation in the relational life of God and the Church.